Enveloped double purse-string versus conventional pancreatico-gastrostomy during Whipple procedure: comparative study at Sohag university onco-surgery program - El-Badry, Ashraf M.; Redwan, Alaa A.; Abusedera, Mohammad A.; Ali, Hitham M. (International Surgery Journal, 2016)
Background:Pancreatico-gastrostomy (PG) is widely applied for restoration of connection between the distal pancreatic remnant and digestive tract during Whipple procedure. Comparative studies on the clinical outcome of various PG techniques are scarce. Methods: Medical records of patients who underwent PG at Sohag University Hospital (November 2012-December 2015) were reviewed. Patients who had PG using our new technique of enveloped double purse-string sutures (EDPS-PG) were compared with control group of conventional transfixing suture PG regarding the postoperative outcome. Results:Twenty-seven patients (18 conventional PG and 9 EDPS-PG) were enrolled. Grade C postoperative pancreatic fistula (POPF) occurred only in the conventional PG group. Patients in the EDPS-PG group needed significantly shorter time before removal of the abdominal drains (p = 0.04), significantly reduced length of hospital stay (p = 0.03) and significantly lower grades of postoperative complications (p = 0.02) compared with the conventional PG group. Postoperative death occurred only in one patient in the control group. No significant difference could be found regarding operative time, postoperative bleeding delayed gastric emptying or bile leak. Conclusions:EDPS-PG is new, simple and safe technique for PG during Whipple procedure and results in significant reduction of POPF and overall complications.